A Sound Approach to Concrete: Transforming Concrete Through Shape and Porosity for Acoustical Reflection, Diffusion, and Absorption. Issue 1 (2nd January 2021) - Butko, Daniel
Abstract : The shape, interior volume, and materiality of the built environment influence occupant perception of sound. Placement and articulation of surfaces directly relate to how sound is reflected, diffused, and absorbed prior to aural reception and comprehension. Researchers experimented with and fabricated prototypical aerated concrete sawtooth panels by manipulating ingredients and form, yielding acoustical properties conducive to speech frequencies (specifically Noise Reduction Coefficients). While acoustical measurements were primarily focused on multi‐use educational spaces, laboratory testing and development of frequency‐responsive porosity revealed data for evidence‐based design applicable to various occupancy types. Attention to the spatial interactions of sound and noise corrected common speech intelligibility and clarity deficiencies by decreased reverberation times, linking surface, form, and spatial volume to reflection, diffusion, and absorption.